2006
DOI: 10.1088/0953-8984/18/23/006
|View full text |Cite
|
Sign up to set email alerts
|

Optical and photoelectric spectroscopy of photorefractive Sn2P2S6crystals

Abstract: Low-temperature studies of the absorption, photoluminescence, photodiffusion and photoconductivity spectra of Sn2P2S6 crystals were carried out in the wide spectral range 0.8–3.5 eV. The position of defect energy levels relative to the crystal energy bands has been determined. It was shown that the photoionization transitions from the valence band to the level with the energy Ev+1.35 eV are caused by the presence of the hole metastable state. In the optical and photoelectric spectra several bands were reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 16 publications
0
15
0
3
Order By: Relevance
“…For measurements at the liquid nitrogen temperature T = 78 K, the samples studied were placed into the optical cryostat, which kept temperature stabilised with the accuracy of ±0.05 K using the temperature regulated cryostat system UTREX. For measurements of photoconductivity in planar samples, the eutectic In-Ga-Sn contacts were attached at the front and back sides of samples [41]. Photoconductivity spectra of In x Tl 1−x I were studied at ambient and liquid nitrogen temperatures for different concentrations of indium (x).…”
Section: Structure Determinationmentioning
confidence: 99%
“…For measurements at the liquid nitrogen temperature T = 78 K, the samples studied were placed into the optical cryostat, which kept temperature stabilised with the accuracy of ±0.05 K using the temperature regulated cryostat system UTREX. For measurements of photoconductivity in planar samples, the eutectic In-Ga-Sn contacts were attached at the front and back sides of samples [41]. Photoconductivity spectra of In x Tl 1−x I were studied at ambient and liquid nitrogen temperatures for different concentrations of indium (x).…”
Section: Structure Determinationmentioning
confidence: 99%
“…At the same time, this material behaves as a wide-bandgap semiconductor with a band-gap energy of E g = 2.31 eV. The wavelengths for the pump-probe experiment were chosen on the basis of the results given in article [25], in which it was shown that, for the electromagnetic radiation with the energy of photons lower than 2 eV, the absorption coefficient in this material is extremely low (≤3 cm -1 ), while, at the energies higher than 2 eV, the absorption coefficient increases rapidly reaching the values on the order of 10 5 cm -1 . Such a behavior is typical of semiconducting materials, as well as the photoconductivity phenomenon, which was studied with SPS in [25,26].…”
Section: Experimental Setup and Techniquementioning
confidence: 99%
“…The energy-level diagram of the SPS crystal is given in [25]. It is shown that the conduction band consists of several narrow subbands.…”
Section: Experimental Setup and Techniquementioning
confidence: 99%
“…Вместе с тем, этот материал проявляет свойства широкозонного полупро-водника с запрещенной зоной E g = 2.31 eV. Выбор длин волн для эксперимента по схеме накачка−зондирование был сделан на основе результатов, приведенных в ра-боте [25], в которой было показано, что для электро-магнитного излучения с энергией фотонов меньше 2 eV коэффициент поглощения в этом материале крайне мал (≤ 3 сm −1 ), в то время как при энергиях выше 2 eV по-глощение быстро возрастает, достигая величин порядка 10 5 сm −1 . Такое поведение характерно для полупровод-никовых материалов, так же, как и явление фотопрово-димости, которое для SPS изучалось в работах [25,26].…”
Section: экспериментальная установкаunclassified
“…Диаграмма энергетических уровней кристалла SPS приведена в работе [25]. Показано, что зона проводимо-сти состоит из нескольких узких подзон.…”
Section: экспериментальная установкаunclassified